ANALYSIS OF THE PRIMARY HEALTH CARE WORK IN THE FIELD OF ANTENATAL CARE. - Juraeva G.T; Akhmedova G. A; Hikmatullaeva L (Scholar Express Journals, 2023)
The World Health Organization (WHO) considers primary health care as one of the components of the health system with significant personnel resources. In October 2003, at the conference in Alma-Ata dedicated to the 25th anniversary of the adoption of the Declaration on Primary Health Care (PHC), it was emphasized that the strengthening of the PHC role will contribute to the further improvement of the health system in providing the population with affordable, high-quality medical care. Moving the center of gravity from curative activities to prevention will improve the health of every citizen and, thereby, of society as a whole. Strengthening of the PHC role in the field of sexual and reproductive health (RH) is one of the most important areas in the further improvement of issues of maternal and child health. In Uzbekistan, RH of the population is one of the priority medical and social areas along with other institutions of the healthcare system. This is confirmed by the adoption of a number of legal acts aimed at regulating relations in the field of protecting the reproductive health of citizens, at further improving the quality of services in this area
Keywords: antenatal care; pregnancy; primary health care; reproductive health